Assembly of nuclear ribonucleoprotein particles during in vitro transcription. - Economidis, I V (1982)
The assembly of heterogeneous nuclear RNA (hnRNA) into ribonucleoprotein (RNP) particles has been investigated during in vitro transcription in isolated nuclei. Approximately 80% of the in vitro transcription observed in mouse Friend erythroleukemia cell nuclei is attributable to the activity of RNA polymerase II. In vitro hnRNA transcripts are assembled into particles having the same properties as the nuclear ribonucleoprotein (hnRNP) particles in which hnRNA is found in vivo. Direct contact of hnRNP proteins with newly transcribed hnRNA was demonstrated by nuclease protection experiments and by the covalent transfer of 32P-labeled nucleotides from [alpha-32P]UTP-labeled hnRNA transcripts to specific proteins by RNA--protein crosslinking followed by nuclease digestion and electrophoresis of the nucleotide-bearing proteins. The availability of an in vitro system for hnRNP assembly opens a new route for investigating the functional relationship between nuclear structure and mRNA processing.